2007
DOI: 10.1634/theoncologist.12-8-904
|View full text |Cite
|
Sign up to set email alerts
|

Trends for Inflammatory Breast Cancer: Is Survival Improving?

Abstract: The purpose of this study was to evaluate whether the survival of women with inflammatory breast cancer (IBC) treated at our institution has improved over the past 30 years. Three-hundred ninety-eight patients with IBC were treated between 1974 and 2005. Patient characteristics and outcomes were tabulated and compared among decades of diagnosis. Survival outcomes were estimated with the Kaplan-Meier product limit method and compared among groups with the log-rank statistic. Cox proportional hazards models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 23 publications
4
62
1
Order By: Relevance
“…Despite significant improvements in the disease-free survival rates of non-IBC (nIBC) patients, IBC patient survival rates remain low, with a 5-year disease-free survival rate of less than 40%, in comparison to the $90% of nIBC (4,(7)(8)(9). The poor prognosis is due to infiltration of tumor emboli that metastasize within the dermal lymphatic vessels of the skin overlying the breast (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant improvements in the disease-free survival rates of non-IBC (nIBC) patients, IBC patient survival rates remain low, with a 5-year disease-free survival rate of less than 40%, in comparison to the $90% of nIBC (4,(7)(8)(9). The poor prognosis is due to infiltration of tumor emboli that metastasize within the dermal lymphatic vessels of the skin overlying the breast (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year survival rate for patients with IBC is o40%, while the 5-year survival rate of all other breast cancers combined is approximately 90%. [1][2][3][4] This poor prognosis can be attributed to a number of factors, including the propensity for misdiagnosis of the disease due to its unique clinical presentation. [5][6][7] In contrast to most breast cancers, IBC is characterized by the lack of discernible primary tumor formation and the accumulation of cancerous epithelial cells in the dermal lymphatic vessels.…”
mentioning
confidence: 99%
“…A review of nearly 400 IBC patients treated at The University of Texas MD Anderson Cancer Center between 1974 and 2005 demonstrated that there has been no significant improvement in prognosis for patients with IBC over the past 30 years. 1 Many recent studies have focused on assessing the efficacy of chemotherapeutic regimens in IBC cells/patients where success had previously been observed only in the treatment of non-IBCs. 9,10 Some progress has been made in understanding the mechanisms underlying the invasive nature of IBC.…”
mentioning
confidence: 99%
“…Significantly higher incidence of loco-regional recurrences are found in IBC patients compared to those with noninflammatory breast cancers. 2 Local recurrence has been linked to the presence of radioresistant Breast Cancer Stemlike Cells (BCSC). These cells, bearing the phenotype of CD44 high /CD24 low/-, resemble normal mammary stem cells in that they are capable of undergoing continuous self-renewal.…”
Section: Introductionmentioning
confidence: 99%